Extraction of Nanocellulose from Yerba Mate Residues Using Steam Explosion, TEMPO-mediated Oxidation and Ultra-fine Friction Grinding. Issue 15 (23rd November 2022) - Gemmer, Ruan Ezequiel; Borsoi, Cleide; Hansen, Betina; Dahlem Júnior, Marcos Aurélio; Francisquetti, Edson Luiz; Rossa Beltrami, Lilian Vanessa; Zattera, Ademir José; Catto, André Luis
ABSTRACT: In this work, we evaluated the extraction of nanocellulose from agro-industrial residue of yerba mate (YM, Ilex paraguariensis, St.Hil) sticks through chemical (bleaching and 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO)-mediated oxidation), physical (steam explosion) and mechanical (ultra-fine friction grinding) treatments, divided into three distinct sequences for method comparison. The results showed that steam explosion as the initial treatment step makes an increase of up to 23% in the crystallinity index of cellulose nanofiber (CNF) in relation to the raw sample. The TEMPO-mediated oxidation resulted in more dispersed CNF, verified by transmission electron microscopy (TEM). Samples treated by steam-explosion and ultrafine grinding showed a higher yield in relation to steam-explosion and oxidative treatment (24.3% versus 16.2% respectively). CNFs with a diameter of 6 nm and a length range of 2200 to 2600 nm were obtained.